KEDUDUKAN DAN STATUS PENDIDIKAN DAN PELATIHAN VOKASI DI DENMARK DAN INDONESIA - Mawaddah A.; Hamsu Abdul Gani; Purnamawati (Program Studi S2 Pendidikan Teknologi dan Kejuruan, 2023)
This research is part of a literature review on the position and status of vocational education and training in Denmark and compares it with vocational education in Indonesia. This research uses a literature research method that is organized systematically, so as to produce quality output. The sources of this literature study are articles totaling 11 articles and government regulations or laws totaling 2 regulations. Based on the results of the review with the help of references, it can be concluded that the 2014 reform in vocational education in Denmark has not been able to approach the target of the desired achievement including the efforts made do not make VET in Denmark attractive to young people. In contrast to Indonesia where every year vocational school enrollment is increasing considering that the opportunities to be ready to work in vocational schools are very large but this is not supported by adequate resources and infrastructure, implementation of regulations that have not been implemented properly and other things that make the learning process ineffective .